Experimental insight into the temperature effects on DC and microwave characteristics for a GaAs pHEMT in multilayer 3‐D MMIC technology. Issue 10 (3rd August 2020) - Alim, Mohammad Abdul; Rezazadeh, Ali A.; Crupi, Giovanni
Abstract: This paper is focused on studying the behavior of a GaAs pseudomorphic high electron mobility transistors (pHEMT) with respect to the temperature. The tested pHEMT is realized using the multilayer three‐dimensional (3‐D) monolithic microwave integrated circuit (MMIC) technology. The analysis is based on temperature‐dependent on‐wafer measurements carried out from 298 K to 373 K. The experiments consist of DC characteristics and scattering parameters in the broad frequency range from 45 MHz to 40 GHz. The effect of the temperature on the measured transistor performance is analyzed in detail and then, to gain a better insight and understanding of the device behavior, the achieved measurements are used for extraction and validation of a small‐signal equivalent‐circuit model for different temperature conditions. This study shows that, by heating the studied device, the observed performance variations depend remarkably on the selected bias condition. In particular, the output current and transconductance are degraded at higher gate‐source voltage and improved as the transistor is driven towards the pinch‐off. This is due to the counterbalancing of temperature‐dependent effects contributing in opposite ways to the resultant behavior of the transistor. Therefore, depending on the given application, an appropriate selection of the bias and temperature conditions is essential to guarantee adequate transistor performance.